Genome-wide association study confirms SNPs in SNCA and the MAPT region as common risk factors for Parkinson disease - Edwards, Todd L. (2010)
Parkinson disease (PD) is a chronic neurodegenerative disorder with a cumulative prevalence of greater than one per thousand. To date three independent genome-wide association studies (GWAS) have investigated the genetic susceptibility to PD. These studies have also implicated several genes as PD risk loci with strong, but not genome-wide significant, associations. In this study, we combined data from two previously published GWAS of Caucasian subjects with our GWAS of 604 cases and 619 controls for a joint analysis with a combined sample size of 1752 cases and 1745 controls. SNPs in SNCA (rs2736990, p-value = 6.7×10(−8); genome-wide adjusted p = 0.0109, odds ratio (OR) = 1.29 [95% CI: 1.17–1.42] G vs. A allele, population attributable risk percent (PAR%) = 12%) and the MAPT region (rs11012, p-value = 5.6×10(−8); genome-wide adjusted p = 0.0079, OR = 0.70 [95% CI: 0.62–0.79] T vs. C allele, PAR% = 8%) were genome-wide significant. No other SNPs were genome-wide significant in this analysis. This study confirms that SNCA and the MAPT region are major genes whose common variants are influencing risk of PD.